O-236 The clinical and morphokinetic factors indicating a risk of pregnancy loss after a euploid embryo transfer. (6th August 2021) - Yuksel, K B; Ozer, G; Duzguner, I N B; Kumtepe, Y; Yelke, H; Kahraman, S
Abstract: Study question: Are there any clinical and morphokinetic factors which may affect the pregnancy outcome after a euploid embryo transfer? Summary answer: Body mass index (BMI), endometriosis, the history of recurrent pregnancy losses and the number of previous frozen-thawed unsuccessful embryo transfer (FET) cycles impact pregnancy outcomes. What is known already: Preimplantation genetic testing for aneuploidy (PGT-A) is largely used for various indications to detect chromosomal abnormalities in assisted reproductive technologies (ART). The most common reason for the first trimester pregnancy losses is chromosomal abnormalities. However, the factors that cause pregnancy loss after a euploid embryo transfer are not fully understood. Study design, size, duration: The pregnancy results of all single euploid embryos tested with next generation sequencing (NGS) in Istanbul Memorial Hospital between January 2017 and March 2020 were evaluated in this single center retrospective cohort study. The cases that resulted in pregnancy below the age of 43 were analyzed according to outcomes; biochemical pregnancy loss (Group 1), clinical pregnancy loss (Group 2) and live birth (Group 3). Participants/materials, setting, methods: The transfer of 2041 single euploid embryos resulted in 1492 pregnancies. The clinical and morphokinetic parameters observed using time lapse imaging (TLI) were compared among the three groups. Main results and the role of chance: The overall pregnancy rate was 73.1%, the rates of biochemical pregnancy losses and clinical losses were 9.7% and 11.4% respectively. The live birth rate was 58.5%. The indications for PGT-A were as follows; recurrent pregnancy losses (RPL) (14.9%), recurrent implantation failure (RIF) (11.7%), advanced maternal age (AMA) (28.6%), a history of abnormal fetal karyotype or single gene defects (12.1%). In 32.6% cases PGT-A was performed to reduce time to pregnancy. There were no differences in terms of female age, AMH, the diagnosis or the duration of infertility, the mean numbers of oocytes retrieved, mature and fertilized oocytes. However, BMI values, the presence of severe endometriosis, including adenomyosis, the history of recurrent pregnancy losses and the number of previous unsuccessful FET cycles were significantly higher in Groups 1 and 2. When pregnancy losses were evaluated according to PGT indications, patients with a history of RPL had a significantly higher pregnancy loss rate (27.8%) compared to the other groups: AMA (19.6%), RIF (19.4%), genetic factors (21.6%) and cases where PGT was performed to reduce time to pregnancy (16.4%) (p < 0.05). When morphokinetic parameters were evaluated, they were found to be not significantly different in the three groups (p > 0.05). Limitations, reasons for caution: The retrospective nature of the data is the major limitation of the study. On the other hand, the strength of the study is the large number of PGT-A tested embryos from a single center which used the same laboratory conditions. Wider implications of the findings: PGT-A is widely used to avoid pregnancy losses. However, BMI values, the presence of severe endometriosis, including adenomyosis, the history of recurrent pregnancy losses and the number of previous unsuccessful FET cycles should be taken into consideration during counselling and/or treatment. Trial registration number: not applicable